The Study of Islam in African Universities: Reflections on Ghana (American Journal of Islam and Society, 2014)
Although not as comprehensive as the articles featured in this special issue,this editorial presents my comments and the results of my survey conductedamong professors and lecturers who teach Islamic studies in Ghanaian universities.For a comparative perspective, similar questions were also sent tocolleagues in Nigeria. I undertook this preliminary research to prepare myselffor a roundtable discussion that was held at the annual African StudiesAssociation meeting (Philadelphia, November 29-December 1, 2012) on“The Study of Islam in African Universities: Is it a Priority?” Based on my ownon-the-ground knowledge and what I gathered from my survey’s respondents,this topic does not seem to be a priority for Ghana’s university administrators(viz., the presidents, vice chancellors, and deans all the waydown to the department heads and their administrative support), students,parents, or policymakers.In general terms, Ghana’s university administrators see no value in supportingthis stream of study because it does not “produce” graduates who canmake constructive contributions to the national agenda of industrial development.The study of religion (or religious studies) in general suffers from thisbias internationally, and religion itself is becoming less popular among youngpeople. Other indications of this low priority are the courses offered in religiousstudies departments and the lack of “suitable” experts. After my presentation,one audience member who had earned a PhD in Islamic studies from a MiddleEastern university, pointed out that he could not find a teaching job in a Ghanaianuniversity. He seemed to believe that his situation had a lot to do with discriminationand bias; however, I was not so sure. He is now an adjunctinstructor in Islamic studies at a local junior college in the Philadelphia area.Of Ghana’s 8 public and 48 private universities,1 only 5 or six 6 have departmentsthat include Islam in their courses listings.2 Apart from the newlyestablished Islamic University College, which is not included here because itis an Islamic university, none of the leading universities offer a major or aminor in Islamic studies. The University of Ghana (Accra) does come close, ...